Impact of SARS-CoV-2 (COVID-19) on pregnancy: a systematic review and meta-analysis protocol - Medeiros, Kleyton Santos (BMJ Open, 2020)
INTRODUCTION: The COVID-19 pandemic, caused by the SARS-CoV-2 virus, has been growing at an accelerating rate, and has become a public health emergency. Pregnant women and their fetuses are susceptible to viral infection, and outcomes in this population need to be investigated. METHODS AND ANALYSIS: PubMed, Web of Science, Embase, CINAHAL, Latin American and Caribbean Health Sciences Literature, clinicaltrials.gov, SCOPUS, Google Scholar and Cochrane Central Controlled Trials Registry will be searched for observational studies (cohort and control cases) published from December 2019 to present. This systematic review and meta-analysis will include studies of pregnant women at any gestational stage diagnosed with COVID-19. The primary outcomes will be maternal and foetal morbidity and mortality. Three independent reviewers will select the studies and extract data from the original publications. The risk of bias will be assessed using the Newcastle-Ottawa Scale for observational studies. To evaluate the strength of evidence from the included data, we will use Grading of Recommendation Assessment, Development, and Evaluation method. Data synthesis will be performed using Review Manager software V.5.2.3. To assess heterogeneity, we will compute the I(2) statistics. Additionally, a quantitative synthesis will be performed if the included studies are sufficiently homogenous. ETHICS AND DISSEMINATION: This study will be a review of the published data, and thus it is not necessary to obtain ethical approval. The findings of this systematic review will be published in a peer-reviewed journal. PROSPERO REGISTRATION NUMBER: PROSPERO 2020: CRD42020181519.